P036 Patients with learning disability, views on the use of a patient-held medication passport. Issue 7 (19th June 2019) - Crook, Joanne; Patel, Deepa; Marvin, Vanessa; Jubraj, Barry
Abstract : Aim: To establish the views of adolescent patients with learning disabilities and their carers, of the patient-held medication passport (My Medication Passport-MMP). Methods: A questionnaire was devised to find out if patients/carers thought a patient-held record of their medications (the MMP) was useful and to suggest improvements as appropriate. The MMP is a patient-held record of medicines use available as a passport sized booklet. 1 MMPs were distributed to patients and carers for them to read and review at a patient focus group. Ethics approval was not required for this study. Results: 20 questionnaires were sent and a total of 17 completed questionnaires were returned (85% response rate). 70% (n=12) of the questionnaires were completed by carers, 24% (n=4) by family members and 1% (n=1) by a patient. 100% (n=17) of carers/patients who reviewed the MMP found it useful. When asked about features they liked about MMP; Seven carers noted the MMP was easy to use; four carers felt MMP was a good way to keep (personal) medicines information up to date; with three further clarifying that it could be used as a 'concise way of keep track (of medicines)' and two specified they liked that 'all the information is in one book'. When Patients/carers were asked for ways MMP could be improved; two carers asked for more space to document past medication, including an area to 'keep track of the behaviours and how it is exhibited because of the medication'; one carer noted that 'some youngsters would benefit from more visual learning' and one asked for a version to be made available via app on smart phone. Limitations included a small sample with limited exposure to MMP. The patient group sampled may not be representative. Conclusion: Passports as tools aim to help patients better manage their medicines and have been successfully used in a patient with learning disability. 2 It is encouraging to see that this small group of patients with learning disability find the MMP useful. Suggested adaptations to MMP for this patient group included it being more visual, and having areas for past medication. Other trials of MMP have suggested that it may require a section surrounding medicines administration. Patients have since been directed to the MMP app which can be downloaded onto a smartphone. There are many opportunities for future work including conducting an evaluation of the MMP in use over time and across different sectors, and to determine what patients actually record in the MMP. References: Barber S, et al. Evaluation of My Medication Passport: a patient-completed aide-memoire designed by patients, for patients, to help towards medicines optimisation. BMJ Open 4(8). https://bmjopen.bmj.com/content/4/8/e005608 Jubraj B. Use of a medication passport in a disabled child seen across many care settings . BMJ Case Reports. 25 February 2015; http://casereports.bmj.com/content/2015/bcr-2014-208033Save